1999
DOI: 10.1097/00005537-199906000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Uses and limitations of fdg positron emission tomography in patients with head and neck cancer

Abstract: For staging purposes, PET is limited by its lack of anatomic detail. However, PET compares favorably with CT and MRI in detecting recurrent/residual cancers. PET imaging complements the more traditional imaging modalities (CT or MRI), especially for an unknown primary cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 15 publications
6
65
0
5
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31] It has also been shown in several studies to have higher predictive values than CT and/or MRI, 21,27,32,33 and better than combined clinical examination and ultrasound. 31 Finally, studies have found that co-registering PET and CT (PET-CT) is even more accurate than PET alone 33,34 ( Table 1).…”
Section: 14mentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31] It has also been shown in several studies to have higher predictive values than CT and/or MRI, 21,27,32,33 and better than combined clinical examination and ultrasound. 31 Finally, studies have found that co-registering PET and CT (PET-CT) is even more accurate than PET alone 33,34 ( Table 1).…”
Section: 14mentioning
confidence: 99%
“…Several retrospective (5)(6)(7)(8) and prospective (9-11) studies have shown that 18 F-FDG PET may be useful in detecting posttreatment recurrent HNSCC and be more effective than physical examination, CT, or MRI in doing so. However, in prior tumor recurrence studies, patients were commonly enrolled if recurrence was suspected.…”
mentioning
confidence: 99%
“…PET (positron emission tomography) with the use of 18-fluorodeoxyglucose in combination with the CT examination is considered by many authors as the method of high efficacy, both in the determination of the primary lesion (40-60%), and staging of the neoplastic process (26,27,28). Greven et al pointed to the limited specificity of 18-FDG PET: the primary lesion was diagnosed in 1 of 13 analysed cases with a high percentage of false positive results (29).…”
Section: Discussionmentioning
confidence: 99%